2019
DOI: 10.1001/jamaoncol.2018.5543
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Immediate vs Deferred Cytoreductive Nephrectomy in Patients With Synchronous Metastatic Renal Cell Carcinoma Receiving Sunitinib

Abstract: patients with primary metastatic renal cell carcinoma (mRCC) have been offered cytoreductive nephrectomy (CN) followed by targeted therapy, but the optimal sequence of surgery and systemic therapy is unknown. OBJECTIVE To examine whether a period of sunitinib therapy before CN improves outcome compared with immediate CN followed by sunitinib. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial began as a phase 3 trial on July 14, 2010, and continued until March 24, 2016, with a median follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
293
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(311 citation statements)
references
References 32 publications
6
293
1
11
Order By: Relevance
“…2 Another randomized study, the SURTIME trial, showed that deferred nephrectomy after three cycles of sunitinib had relatively longer OS than immediate nephrectomy (32.4 vs 15.0 months), because more patients received sunitinib in the deferred nephrectomy group. 17 Furthermore, a number of retrospective studies showed the benefit of cytoreductive nephrectomy, including the present study. 12,13,15,[18][19][20][21] Thus, cytoreductive nephrectomy is still expected to prolong survival, especially in patients with systemic therapy and long survival expectancy, so that the appropriate patient selection for nephrectomy is warranted.…”
Section: Discussionsupporting
confidence: 55%
“…2 Another randomized study, the SURTIME trial, showed that deferred nephrectomy after three cycles of sunitinib had relatively longer OS than immediate nephrectomy (32.4 vs 15.0 months), because more patients received sunitinib in the deferred nephrectomy group. 17 Furthermore, a number of retrospective studies showed the benefit of cytoreductive nephrectomy, including the present study. 12,13,15,[18][19][20][21] Thus, cytoreductive nephrectomy is still expected to prolong survival, especially in patients with systemic therapy and long survival expectancy, so that the appropriate patient selection for nephrectomy is warranted.…”
Section: Discussionsupporting
confidence: 55%
“…Leur pronostic est péjoratif, même lorsqu'elles sont opérées rapidement, particulièrement en cas de thrombus veineux [9]. Il est donc recommandé d'opérer ces tumeurs en priorité ; • concernant la néphrectomie cytoréductrice, les essais Carmena et Surtime indiquent que le traitement médical seul n'est pas inférieur à la néphrectomie associée au traitement médical et que la néphrectomie différée n'est pas associée à une moins bonne survie [10,11] Le bénéfice du standard actuel de traitement reposant sur l'association ipilimumab-nivolumab doit être mis en balance avec le risque de toxicité sévère dans le contexte de réduction de l'accès à un service de réanimation L'emploi du sunitinib par défaut est sub-optimal mais peut se discuter dans ce contexte Les patients de pronostic intermédiaire avec faible charge tumorale et asymptomatiques pourraient être traités par TKI Pour les patients de mauvais pronostic et en mauvais état général (PS ≥ 2), un traitement palliatif exclusif peut être privilégié les patients de bon pronostic. Tous ces éléments incitent à prioriser : soit la surveillance en cas de faible volume tumoral, soit le traitement médical premier et la discussion secondaire de la chirurgie en fonction de l'évolutions du patient et de l'épidémie ;…”
Section: Cancer Du Rein Localisé Et Localement Avancéunclassified
“…36 In addition, another randomized trial, the SURTIME trial, which compared mRCC patients treated with sunitinib therapy before CN with those with immediate CN followed by sunitinib, showed that there was no significant difference of the progression-free rate between these two groups. 37 The effect of presurgical sunitinib treatment might provide some information on predicting the benefit of CN. As the number of new agents is increasing, the impact of CNx and patients' selection for CNx needs to be discussed further.…”
Section: Prognostic Factors For Mrcc Patients Treated With Targeted Tmentioning
confidence: 99%